Lyso-thermosensitive liposomal doxorubicin: an adjuvant to increase the cure rate of radiofrequency ablation in liver cancer. (August 2011) - Poon, Ronnie TP; Borys, Nicholas
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer death worldwide. No more than 30% of HCC patients are considered suitable for curative treatment because of tumor size and severity of liver impairment, among other factors. Radiofrequency ablation (RFA) monotherapy can cure small (<3 cm) HCC tumors. An adjuvant that interacts synergistically with RFA might enable curative therapy for many HCC patients with lesions >3 cm. Lyso-thermosensitive liposomal doxorubicin (LTLD) consists of the heat-enhanced cytotoxic doxorubicin within a heat-activated liposome. LTLD is infused intravenously prior to RFA. When heated to >39.5°°C, LTLD releases doxorubicin in high concentrations into the tumor and the tumor margins. The RFA plus LTLD combination has shown a statistically significant dose––response effect for time to treatment failure in a Phase I trial in which most subjects (62.5%) had tumors >3 cm. RFA plus LTLD is currently being evaluated in a 600-patient randomized, double-blind, dummy-controlled trial.